Impairments in the Visual Processing of Global Biological Motion Cues in Down Syndrome. (November 2017) - Riddell, Hugh; Tolentino-Castro, J. Walter; Wagner, Heiko; Lappe, Markus
Down syndrome (DS) is one of the most common chromosomal disorders and is often associated with a number of motor and cognitive impairments. Little research has been dedicated to investigating the perceptual abilities of individuals with DS. The visual processing of biological motion has been shown to be impaired in DS. It has been proposed that these impairments may stem from an inability to process the global patterns of full-body motion produced by a moving actor; however, this has not been explicitly investigated. We tested groups of participants with and without DS on a task requiring the visual discrimination of point-light walkers from spatially scrambled versions of point-light walkers. Participants with DS demonstrated poorer performance and slower reaction times on the task than healthy controls. From these results, we conclude that biological motion processing is impaired in DS and that this deficit is related to an inability to integrate global configural cues. In a second experiment, individuals with DS were able to discriminate the direction in which laterally translating walkers moved, suggesting that the global motion processing deficit observed in Experiment 1 is specific to biological motion recognition and does not generalise to other types of global motion.